COMMUNICATION STRATEGY OF THE NORTH SUMATRA KPOTI ORGANIZATION IN REVITALIZING TRADITIONAL SPORTS AMIDST THE CURRENT OF MODERNIZATION - Akhsanul Hidayat; Yusniah Yusniah (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze the organizational communication strategies of KPOTI North Sumatra in revitalizing traditional sports amid the currents of modernization. Using a descriptive qualitative approach and a single case study design, data were collected through in-depth interviews, participatory observation, and media documentation. The data analysis followed the Miles, Huberman, and Salda